Damage detection in steel bars using ultrasonic guided waves: An experimental and analytical study - Sharma, Shruti; Bhise, Prashant C.; Mukherjee, Abhijit (Journal of Structural Engineering, 2025)
One of the major causes of catastrophic failures in reinforced concrete structures such as bridges, dams and buildings is the deterioration of reinforcing bars. If the degradation in the reinforcing bars remains unnoticed, it further accelerates and causes huge loss of life and property. Towards development of a damage detection methodology for such systems, an attempt has been made by first developing a damage monitoring technique for steel bars in air. It has been done by utilising ultrasonic guided waves. Experimentally, both pulse transmission and pulse echo techniques have been adopted and the time of flight and signal attenuation have been observed to locate and quantify the damage accurately. An efficient numerical technique, the spectral element method, has been used for numerical modelling of the problem. The numerical results have been validated with the experimental observations.